Successful pregnancy outcome with a large ruptured juvenile granulosa cell tumor: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Juvenile granulosa cell tumors (JGCTs) are rare sex cord stromal tumors diagnosedmainly in premenarchal girls and women younger than 30 years.Case presentation: A 19-year-old primigravida at 36 weeks of gestation presented to the labor ward withcomplaints of generalized abdominal pain, headaches, and reduced fetal movements for two days.Ultrasound revealed a left-sided 15.7 by 15 cm large cyst and a solid mass of increased vascularity withmaternal ascites. The biophysical profile of the fetus was 4/8 (no movement or tone but the presence ofrespiration and amniotic fluid). An emergency exploratory laparotomy was performed, and intraoperativefindings revealed a massive torsed right ovary with a ruptured ovarian mass with grossly edematous andnecrosed fallopian tubes. Following a safe cesarean section delivery of the fetus, a right salpingo-oophorectomy with cystectomy was performed. The histopathological results confirmed the diagnosis ofJGCT FIGO stage IC2. Postoperatively, the patient was treated with six sessions of chemotherapy(cisplatin and paclitaxel). Post-chemotherapy magnetic resonance imaging showed normal abdominalviscera with minimal free fluid in the posterior cul de sac and a normal left ovary. Inhibin B levels droppedto 3.17, and the patient is on follow-up for the next 5 years with repeated tumor marker testing andcomputed tomography scans.Conclusion: JGCT is a very uncommon pregnancy tumor, and aggressive treatment is necessary foradvanced-stage tumors such as the one in this case to prevent recurrence or even death.